2004
DOI: 10.1191/0961203304lu2009oa
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies associated with reproductive failure

Abstract: Autoimmune factors are involved in some of the cases of reproductive failure. These factors entail several autoantibodies, especially in patients having systemic lupus erythematosus (SLE) or the antiphospholipid syndrome (APS). These autoantibodies include mainly antibodies directed to phospholipid such as cardiolipin, phosphatidylserine, phosphatidylethanolamine or phospholipids binding glycoproteins such as beta2glycoprotein-I, annexin V, prothrombin and protein-Z. There are also some other autoantibodies di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 61 publications
1
35
1
Order By: Relevance
“…In the present study, the significantly higher ACL IgM positivity rate in women with primary infertility was consistent with that reported by other workers [12] [14]. This may be due to the ability of ACL antibodies to cause tiny blood clots, preventing blood from flowing to the reproductive organs or placenta [6]- [8] [19]. It has been found that the passive transfer of the purified ACL IgM antibodies was associated with lower fecundity and/or an increased rate of embryo absorptions (equivalent to primary infertility) [20].…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the significantly higher ACL IgM positivity rate in women with primary infertility was consistent with that reported by other workers [12] [14]. This may be due to the ability of ACL antibodies to cause tiny blood clots, preventing blood from flowing to the reproductive organs or placenta [6]- [8] [19]. It has been found that the passive transfer of the purified ACL IgM antibodies was associated with lower fecundity and/or an increased rate of embryo absorptions (equivalent to primary infertility) [20].…”
Section: Discussionsupporting
confidence: 81%
“…When exposed to reactive oxygen species, LDLs undergo oxidation, a complex process that leads to formation of oxLDL and a number of products derived from lipids through peroxidation and fragmentation. Several lines of evidence support the view that oxLDLs are implicated in atherogenesis (for review, see Steinerova et al, 3 Horkko et al, 4 and Shoenfeld et al 5 ). Oxidative modification of LDL can be a prerequisite for rapid accumulation of LDL in macrophages and foam cell formation, and in vitro, oxLDLs were found to resemble biochemically and immunologically the LDL extracted from atherosclerotic lesions.…”
mentioning
confidence: 75%
“…We recently reported in pregnant SLE women a strong association among HPRL, lupus anticoagulant (LA) levels, active disease, and poor pregnancy outcome (preterm birth and low birth weight) [71]. In fact, multiple autoantibodies are involved in patients with SLE and antiphospholipid syndrome with reproductive failure [72]. The association of HPRL and LA during pregnancy, and positive LA at the end of pregnancy, supports the notion that PRL is a potent immune stimulator.…”
Section: Prolactin Systemic Lupus Erythematosus and Pregnancymentioning
confidence: 90%